SOLUSI KOMUNIKASI BERTENAGA MATAHARI - lande, nelly malik (Jurnal Sains dan Teknologi Indonesia, 2008)
Indonesia is a country that contains by some large islands and thousand small islands. It means a communication very important. Increasing in the market demand, especially communication serves make some vendor to produce aninstrument called Base Transceiver Station (BTS). BTS is very important in network telecommunication because it connect telecommunication operator with its costumers. But the problem to operate BTS in far region is electrical power supply. For handling its problem is by using BTS with SESF, or often called Pembangkit Listrik Tenaga Surya Fotovoltaik (PLTS Photovoltaic), where it claimed need less energy. Because it took a lot cost for photovoltaic instrument, this paper will descript how to design hybrid system, a union of photovoltaic and diesel.